Grain-distribution of surface sediments in the Argentine basin, R/V METEOR cruises M23-2, M29-2, M46-3 and M49-2 - Elda Miramontes; Ruben Kantner; Tilmann Schwenk; Gastón Kreps (PANGAEA, 2024)
The aim of this study is to better understand the oceanographic processes at the origin of contourite features. The samples were collected during four cruises onboard the R/V METEOR: M23-2 in 1993, M29-2 in 1994, M46-3 in 2000 and M49-2 in 2001. The measurements were performed to complement previous analyses and therefore, not all cores from these cruises have been measured. Grain size analyses were performed on bulk sediment samples with a Beckman Coulter Laser LS 13 320 at MARUM laboratories using Sodium hexametaphosphate as a dispersant.